Thermal convection in electrochemical cells. Boundaries with heterogeneous thermal conductivity and implications for scanning electrochemical microscopy - Novev, J; Compton, R (Royal Society of Chemistry, 2017)
We investigate the heat transfer in a cylinder-shaped electrochemical cell with solid, thermally insulating walls. The cell is filled with a liquid and a solid substrate that is thermostated from below is situated at its base. The initial temperature of the liquid is different from that of the substrate so as to mimic imperfect thermostating in an electrochemical experiment; as heat transfer acts to diminish the temperature difference between the two, natural convection ensues. The influence of inhomogeneities in the thermal conductivity of the solid is studied – numerical simulations of the heat transfer in the system are conducted for substrates that are comprised of a thermally conductive material, an insulating one or a combination thereof. It is shown that the substrate structure strongly influences the structure and intensity of the natural convective flows emerging in the system. The present work demonstrates that under the idealized conditions under consideration, depending on the substrate structure, natural convection due to imperfect solution thermostating may give rise to flows whose local velocity can reach values as high as 10-3 m∙s-1. Moreover, as comparison between cells of two different radii shows, both the intensity and the temporal evolution of the flows arising in this system are highly sensitive to the precise geometry of the experimental cell. These results can have far-reaching consequences for the interpretation of results from experimental techniques such as scanning electrochemical microscopy.